Makalah Industri Substitusi Impor Dan Persaingan Industri Pada Pembangunan Industri - Virgi Ainun Iqbal; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Import substitution industrialization (ISI) is one of the industrial development strategies that has been implemented by many developing countries, including Indonesia. This strategy aims to reduce dependence on imported consumer and capital goods, as well as create jobs and increase domestic value added. In the early stages of its implementation, ISI has successfully driven industrial growth in Indonesia. However, along with technological development and global competition, ISI faces various challenges, one of which is competition from industries in other countries. Industrial competition is one of the important factors that affects industrial development. Healthy competition can encourage industries to innovate and improve efficiency, making them more competitive in the global market. This paper discusses the relationship between ISI and industrial competition in industrial development. This paper also discusses various policies that can be implemented to improve the competitiveness of Indonesian industries.